Genetic, chemical and agronomical characterization of husk tomato advanced lines - González-Chavira, Mario Martin (2019)
Introduction. Knowledge about the genetic, chemical and morphological diversity that exists between individuals and populations is very useful in breeding programs, because it facilitates the organization of the material and the appropriate selection of superior genotypes for the development of an improved population. Objective. The aim of this research was to make a genetic, chemical and agronomic characterization in twenty advanced husk tomato lines (Physalis ixocarpa Brot.), belonging to the vegetable breeding program of the Campo Experimental Bajío (CE-Bajío), of the Instituto Nacional de Investigaciones Forestales, Agrícolas y Pecuarias (INIFAP), México. Materials and methods. During the spring-summer and autumn-winter 2017, the genetic variability was quantified with molecular markers of DNA, type AFLP (Amplified Fragment Length Polymorphisms), likewise, the phenolic and tomatidine compounds in the fruit were determined, and agronomic traits like germination percentage, number of fruits per plant, weight of the fruit, equatorial and polar diameter per fruit, and fruit yield were determined. A general average of similarity between the genotypes of 0.86 was obtained. Results. A general similitude mean between genotypes of 0.86 was obteined. According to the genetic relationships, a geographic pattern was identified and genotypes 4 and 70 were detected as possible progenitors of improved hybrids. Chemical diversity indicated that the fruits flavonoids content in L-86 was the highest (51.1mg EAG/100g), phenols (396.8 mg EAG/100 g) and anthocyanin’s (7.22 mg EAG/100g) for L-182 and tannins (188.4 mg EAG/100 g) for L-97, while tomatidine (2.23-3.81 mg EAG/100 g) was higher in green fruits than purple fruits. The agronomic results indicate that the lines fruit yield ranged from 11.4 to 47.6 t/ha, the 20% of the lines has a superior yield than the national mean yield (40 t/ha), The L-37 was noticeable, since it has the highest fruit yield with 47.6 t/ha, and has the highest number of fruits number per plant, equatorial and polar diameters, and germination rate (93.3%). Conclusion. Based on the results the lines 37, 25, 27 and 167 are positioned as lines with potential for commercial use and as parental lines.